Pendampingan Penerapan Digital Marketing Sebagai Strategi Pemasaran Pada UMKM Bolu Telur Crispy - Andhita Risko Faristiana; Afif Nur Fadhila; Nadila Eka Watiningtyas; Salsabila Fabiyana (Universitas Maritim AMNI Semarang, 2023)
Today's modern technology continues to advance and develop, especially social media which has a huge impact on people's lives. Advances in technology also have an impact on marketing, especially in the buying process. Digital Marketing is a marketing strategy that can reach the wider community, from the top to the bottom. In this study, there are problems faced by the owners of UMKM Crispy Egg Cake, one of which is the lack of knowledge about how to apply digital marketing as a place to promote their products, so the marketing plan in this study aims to develop UMKM Crispy Egg Cake in Bungkuk Village, Parang District, Regency Magetan in terms of implementing digital marketing as a place to promote products, so that they are better known by the public out there. Research in this training uses the ABCD method or this training uses the ABCD approach, namely Asset Based Community Development, which prioritizes the use of assets and potential that exist around and are owned by the community. The results of this study can prove that by assisting the implementation of digital marketing as a marketing strategy, crispy egg cake owners know more about the benefits and how to use technology, especially in terms of digital marketing to advertise or sell their crispy egg cake food products, so by using digital marketing This sales turnover and public interest in buying crispy egg cakes has increased. In addition, sellers also gain a lot of useful knowledge about digital marketing technology and can compete in the market with other similar or different food products